إضراب الثمانية أيام يرفع صوت الجزائر إلى مبنى نيويورك - لوافي, سومية (جامعة الوادي University of Eloued, 2017)
يعتبر إضراب الثمانية أيام من 28 جانفي إلى 04 فيفري 1957 حدثا بارزا في مسيرة الثورة التحريرية الجزائرية، الذي كان نتيجة للنجاح الكبير الذي حققه مؤتمر الصومام التاريخي، حيث نظم العمل الثوري بالداخل والخارج ووضع قواعد تنظيمية للعمل الميداني العسكري والسياسي والإداري والاجتماعي. كما تزامن تنظيم هذا الحدث التاريخي الهام والانتصارات الكبيرة التي حققها جيش التحرير الوطني على العدو، أما في الإطار السياسي الدولي فقد صادف إدراج القضية الجزائرية في برنامج الأمم المتحدة خلال دورتها الثانية عشر. أكد الشعب الجزائري عبر استجابته لنداء الإضراب أنه متمسك بالثورة، ومرتبط بجبهة التحرير الوطني كممثل شرعي ووحيد له، وكان الإضراب فرصة لوكالات الأنباء ومراسلي الصحف الأجنبية لكشف الصورة الواقعية التي يحياها الشعب الجزائري في ضل الاحتلال، وإيصالها للرأي العالمي، وكذلك الأساليب القمعية التي تستخدمها السلطات الفرنسية لإفشال الإضراب الذي كان بمثابة انتفاضة شاملة اندفع فيها الشعب وحمل صوت الجزائر عاليا إلى مبنى نيويورك، أين فتح النقاش حول القضية الجزائرية خلال الدورة الثانية عشر لهيئة الأمم المتحدة. The strike the eight days 28 January to 04 February 1957 event a prominent in March of the revolution editorial Algerian, who was the result of success great achieved conference SOMMAM historical, where systems work revolutionary at home and abroad and regulations to work field military and political and administrative and social. As synchronization organizing this historic event important victories large achieved by the national liberation Army on the enemy, either in the frame international political have encountered the inclusion of the case of Algerian in the United nations program throught its second ten. Confirmed the Algerian people across its response to call the strike that adheres revolution, and is linked to the Front National Liberation, sole legitimate representative of him, and the strike was an opportunity for news agencies and correspondents of foreign newspapers to expose the photo-realism being experienced by the Algerian people lost in the occupation, and delivery of world opinion, as well as the repressive methods used by the French authorities to thwart the strike which served as a comprehensive uprising pushed the people and carry a high voice Algeria to New York building, where open debate on the Algerian issue during the twelfth session of the United Nations.
Keywords: نيويورك، الثورة التحريرية الجزائرية، إضراب الثمانية أيام